Gestão de resíduos sólidos oriundos de alagamentos e inundações: uma avaliação sobre legislação e instrumentos de gestão em Belo Horizonte - MG - Mariana Fernandes Barboza (2016)
In nature occur various phenomena that are considered part of Earths geodynamics responsible for structuring the landscape, however, when these phenomena reach a social system it can cause impacts and damage to people and their properties. When a natural disaster strikes a community a huge amount of waste can be generated, considering the inefficiency of existing systems even in normal times, in the face of natural disasters such systems tend to be deeply affected. Some reports though show that when properly managed such waste can become a valuable resource to the recovery and reconstruction of the affected areas playing a positive role to communities in social and economic ways. Once it is found in Literature review only guides associated to technical issues about the disaster waste management the development of public policies it is necessary to address the components related to the efficiency of the system, such as: planning, legislative consideration and costs involved in the process in order to minimize the possible impacts and avoid the overloading of the management system in post disaster situations. This project seeks an assessment of the Brazilian legislation, in Belo Horizonte specifically the idea is to better understand how the responsible organizations act against such situations and what is their involvement with the affected communities. The results indicate a recent legislation with rare link between natural disaster and waste management, their guidelines are independent and still very ineffective especially considering solid waste management. In Belo Horizonte there is a structure considered the model for facing natural disasters, the Grupo Especial de Áreas de Risco which gathers the responsible actors for such actions in the city. However there are still some difficulties of communication and responsibilities due to the existence of personal and organizational interests above the public welfare. In addition there is a notable lack of involvement from the government in relation to affected communities with many actions just bordering on formality with little or no effectiveness in the view of those who are affected.